(3TQM GdWGhSj Ydi GdMGhj GdUZjQs - (3VjGAGdOjf eMeO Hf CHj HcQ Hf GdWGhSjs; (3YHO GdZaGQ Hf YHO GdcQje Hf YHO GdZaGQ GdbRhjfj, fLe GdOjf,J (B665 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf abgGA gPG GdYUQ deG TZah HOQGSI GdcJGH GdehShe HGdMGhj Medfj Pdc Ydi Cf CTQM dge TQMkG jHdZhf Hg fgGjI GdeWdH s
(3BNQgG (B:s
(3dCf CMOgeG djS HGdJUOjb Chdi ef GdCNQhGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs